2011
DOI: 10.1890/10-0489.1
|View full text |Cite
|
Sign up to set email alerts
|

Monarch butterfly migration and parasite transmission in eastern North America

Abstract: Abstract. Seasonal migration occurs in many animal systems and is likely to influence interactions between animals and their parasites. Here, we focus on monarch butterflies (Danaus plexippus) and a protozoan parasite (Ophryocystis elektroscirrha) to investigate how host migration affects infectious disease processes. Previous work showed that parasite prevalence was lower among migratory than nonmigratory monarch populations; two explanations for this pattern are that (1) migration allows animals to periodica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
182
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 151 publications
(196 citation statements)
references
References 41 publications
13
182
1
Order By: Relevance
“…Just how representative A. gamma is of other migrant insects is a matter for future study, but given the similarities in the migration strategies of A. gamma to those of other insects in Europe (24,34), Asia (21), North America (3,5,19,20), and Australia (8,35), it is very likely that the results of the present study will be applicable to a wide range of migrants. We conjecture, therefore, that during a time when most sedentary Lepidoptera (36,37) and many migrant birds (38,39) have experienced dramatic declines, the shared traits of high fecundity (40), polyphagy (26), year-round breeding (26), reduced disease and parasite loads (41,42), and efficient strategies for the use of windborne transport (43) to exploit widely dispersed seasonal resources are the principal factors that have enabled the recent temperature-related range expansions and population increases observed in many species of migrant Lepidoptera (44). Considering the pest status of A. gamma (and many other species of migrant moths), which is facilitated by their polyphagy, it is certainly germane to increase our understanding of the migration systems of such species.…”
Section: Resultsmentioning
confidence: 99%
“…Just how representative A. gamma is of other migrant insects is a matter for future study, but given the similarities in the migration strategies of A. gamma to those of other insects in Europe (24,34), Asia (21), North America (3,5,19,20), and Australia (8,35), it is very likely that the results of the present study will be applicable to a wide range of migrants. We conjecture, therefore, that during a time when most sedentary Lepidoptera (36,37) and many migrant birds (38,39) have experienced dramatic declines, the shared traits of high fecundity (40), polyphagy (26), year-round breeding (26), reduced disease and parasite loads (41,42), and efficient strategies for the use of windborne transport (43) to exploit widely dispersed seasonal resources are the principal factors that have enabled the recent temperature-related range expansions and population increases observed in many species of migrant Lepidoptera (44). Considering the pest status of A. gamma (and many other species of migrant moths), which is facilitated by their polyphagy, it is certainly germane to increase our understanding of the migration systems of such species.…”
Section: Resultsmentioning
confidence: 99%
“…For example, Bartel et al (2011) demonstrated that the monarch protozoan parasite Ophryocystis elektroscirrha prevalence increased during the host breeding season. However, it was also determined that monarchs sampled at two overwintering sites in Mexico had lower parasite prevalence than those sampled at summer breeding sites (Bartel et al, 2011).…”
Section: Natural Enemies: Role Of Pests Pathogens and Diseasesmentioning
confidence: 99%
“…For example, Bartel et al (2011) demonstrated that the monarch protozoan parasite Ophryocystis elektroscirrha prevalence increased during the host breeding season. However, it was also determined that monarchs sampled at two overwintering sites in Mexico had lower parasite prevalence than those sampled at summer breeding sites (Bartel et al, 2011). Similarly, Altizer et al (2000) determined that non-migratory monarchs in southern Florida that continuously breed were over 70% parasite infested, while Western monarchs that migrate moderate distances to overwintering sites were 30% parasite infested and Eastern monarchs that migrate to Mexico were less than 8% parasite infested over a 30-year timespan.…”
Section: Natural Enemies: Role Of Pests Pathogens and Diseasesmentioning
confidence: 99%
“…Global climate change, habitat loss owing to development and pesticide-induced loss of host and nectar plants, and disease all have been suggested as threats to butterfly populations (e.g., McLaughlin et al 2002;Bartel et al 2011;Preston et al 2012;Pleasants and Oberhauser 2013). These issues are not unique to butterflies.…”
Section: Introductionmentioning
confidence: 99%